APPLICATION ON THE WORKPLACES HAZARDS MEASUREMENT IN A BAKERY UNIT (Journal of Engineering Studies and Research, 2017)
The workplaces, where human activity takes place, is characterized by some complex factors that can affect the health of employees. These factors (temperature, humidity, noise, vibration, toxic substances, lighting, particulate matter etc.) can also be generalized as dangerous factors or workplaces hazards [1, 2, 3, 4]. In this article are presented some results obtained after workplaces hazards measurements in a production and sales bakery unit for the parameters: O2, SO2, CO, NH3, temperature, humidity, suspension powders, VOC. The values of the measured parameters particulate matter (0.17 mg/m3 - 0.30 mg/m3) respectively volatile organic compounds (0.8 ppm ÷ 21.1 ppm) were below the maximum allowable concentrations, which indicates a safe workplaces for employees. The other parameters measured values, respectively temperature and humidity, were between 22.100C - 29.20 C for temperature and 47% - 53% for humidity.
Keywords: workplaces hazards; particulate matter; volatile organic compounds; temperature; humidity